HUBUNGAN ANTARA USIA, DERAJAT KETULIAN, DAN ONSET TULI MENDADAK DENGAN PERBAIKAN PENDENGARAN MENGGUNAKAN HYPERBARIC OXYGEN THERAPY DI RUMAH SAKIT ANGKATAN LAUT DR. MINTOHARDJO TAHUN 2016-2019 - Savira Chrisna Dewi, (2020)
Sudden deafness is sensorineural hearing deterioration at least 30 dB occuring within 72 hours. One of management of sudden deafness hyperbaric oxygen therapy. HBOT is a therapy where a person breathes with 100% oxygen in a room with pressure more than 1 ATA. Its intended to improve oxygenation in the cochlea so that hearing improvement is achieved, which determined by several prognostic factors. This aim of this study is to determine relationship between age, degree of hearing loss, and onset of sudden deafness with hearing improvement using hyperbaric oxygen therapy at Dr. Mintohardjo Naval Hospital in 2016-2019. The cross-sectional study design was used in this research of 36 sudden deafness patients selected by total sampling method. Age cannot be assessed because the data is constant. Fisher's alternative test results showed no relationship with the degree of hearing loss with hearing improvement (p-value 0,307). Onset of sudden deafness as a prognostic factor showed no relationship with hearing improvement with (p-value 0,559). The degree of hearing loss and onset of sudden deafness which is referred to as a good prognostic factor for hearing improvement in sudden deafness treated with HBOT, in this study did not show any significant relationship.